Kebijakan Hukum Pemberian Amnesti - Dwi Novantoro; Azaris Pahlemy; Arief Amrullah; Fendi Setyawan (Jurnal Hukum Lex Generalis, 2025)
This journal uses a normative legal research method. Amnesty is an act of pardon or removal of punishment granted by the President to individuals or groups of individuals who have committed certain criminal acts. Based on Emergency Law Number 11 of 1954, amnesty results in the removal of all criminal consequences for the person granted amnesty. Amnesty and legal certainty are interrelated, because legal certainty is essentially the main objective of law. Emergency Law No. 11 of 1954 on Amnesty and Abolition is considered to be inconsistent with the development of modern constitutional law because there are no implementing regulations for the granting of amnesty by the President, there are no restrictions or criteria regarding what is meant by the interests of the state by the President in granting amnesty, there is no time limit for granting amnesty to perpetrators of criminal acts, and there are no provisions governing the granting of amnesty to defendants as a result of decisions at the District Court level, the appeal level at the High Court, or the cassation level at the Supreme Court.